Parenting perceptions and stress at treatment intake among families of children with autism. Issue 2 (26th September 2021) - Mire, Sarah S.; Benoit, Julia S.; Fritz, Jennifer N.; Racine, Madeline D.; Fein, Rachel H.; Raff, Natalie S.; Rosenbrock, Georgina; Dawson, Kyle
Abstract: Objective: To identify caregiver cognitions and perceptions that may contribute to parenting stress among families of children with autism spectrum disorder (ASD) who receive treatment for severe behaviors. Background: Caregivers of children with ASD and comorbid problem behaviors often report significantly elevated stress, but contributors to this phenomenon are not well understood. Caregiver cognitions and perceptions potentially explain such high stress and, therefore, may represent a malleable intervention point that could positively affect treatment outcomes and whole family well‐being. Method: Caregivers seeking function‐based treatment for their children at a community‐accessible clinic ( n = 29) completed standardized measures of parenting stress and of perceptions about ASD and about child behavior severity. Results: Parenting stress measured at intake did not differ between the Elevated and Within Normal Limits groups in terms of child or caregiver demographics, such as household income or ethnicity. However, caregiver negative feelings associated with an ASD diagnosis were significantly higher in the Elevated group, and caregivers in the Elevated group perceived their children's behaviors as more severe, even though all children were being treated for severe behavior problems. Conclusion: Findings suggest that a key differentiator between parents who report elevated self‐reported stress at intake and those who do not are caregivers' cognitive representations of their child's diagnosis and behavioral severity. Implications: Aligned with psychological constructivism, understanding the role of caregivers' perceptions among ASD‐affected families may aid in better tailoring interventions, which ultimately may improve treatment retention and enhance treatment outcomes.